2016
DOI: 10.1038/ejcn.2016.114
|View full text |Cite|
|
Sign up to set email alerts
|

The nutritional quality of foods carrying health-related claims in Germany, The Netherlands, Spain, Slovenia and the United Kingdom

Abstract: Backgroung/Objectives:Compares the nutritional quality of pre-packaged foods carrying health-related claims with foods that do not carry health-related claims.Subject/Methods:Cross-sectional survey of pre-packaged foods available in Germany, The Netherlands, Spain, Slovenia and the United Kingdom in 2013. A total of 2034 foods were randomly sampled from three food store types (a supermarket, a neighbourhood store and a discounter). Nutritional information was taken from nutrient declarations present on food la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 27 publications
(25 reference statements)
8
43
3
Order By: Relevance
“…Nutrition claims were indeed the most prevalent type of claim found in the Brazilian packaged food supply, covering almost a third of the assessed products as found in other countries [19][20][21]36,37]. Health claims were also quite prevalent and were found in 22% of the assessed products.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nutrition claims were indeed the most prevalent type of claim found in the Brazilian packaged food supply, covering almost a third of the assessed products as found in other countries [19][20][21]36,37]. Health claims were also quite prevalent and were found in 22% of the assessed products.…”
Section: Discussionmentioning
confidence: 84%
“…Nutrition claims were found in 32% of the sweetened dairy products, whereas health claims were found in 34% of the same products. In a study conducted in five European countries, nutrition and/or health claims were found in 46% of the dairy products-the largest proportion among the studied products [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second limitation is the approach used to classify nutrition claims. For example, this study classified both nutrient content claims and health claims as nutrition claims; however, other studies have used an international standardized nutrition labelling taxonomy to overcome the differences between regulations among countries [58][59][60][61], which can facilitate multi-country comparisons in the use of nutrition-related claims. FLIP 2013 did not capture products sold in value chain retailers, convenience stores and neighborhood stores, therefore some products available for purchase were probably missed, which might have included specialty products.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, different types of claims have been studied worldwide [3,24,[58][59][60][61][62][63], although their impact on consumers' health may be small [9]. Perhaps this is because claims are being used more as a marketing strategy by manufacturers [9].…”
Section: Discussionmentioning
confidence: 99%